A sustained release of alendronate from an injectable tetra-PEG hydrogel for efficient bone repair - Chang, Shuai; Li, Chao; Xu, Nanfang; Wang, Jiedong; Jing, Zehao; Cai, Hong; Tian, Yun; Wang, Shaobo; Liu, Zhongjun; Wang, Xing (Frontiers in Bioengineering and Biotechnology, 2022)
Significant efforts on construction of smart drug delivery for developing minimally invasive gelling system to prolong local delivery of bisphosphonates are considered as promising perspectives for the bone-related diseases, which provide the hydrogels with unique bioactivities for bone repair in clinic. Herein, we have constructed an alendronate (ALN)-conjoined injectable tetra-PEG hydrogel with excellent biocompatibility, uniform network, and favorable mechanical properties in one-pot strategy. In views of the quick ammonolysis reaction between N-hydroxysuccinimide (NHS)-ester of tetra-PEG-SG and amine groups of tetra-PEG-NH2 polymer and ALN molecules, the uniform networks were formed within seconds along with the easy injection, favorable biocompatibility and mechanical properties for hydrogel scaffolds. On account of the simultaneous physical encapsulation and chemical linkage of the ALN within the hydrogels, the ALN-conjoined tetra-PEG hydrogel exhibited a sustained drug release delivery that could persistently and effectively facilitate viability, growth, proliferation, and osteogenesis differentiation of stem cells, thereby allowing the consequent adaptation of hydrogels into the bone defects with irregular shapes, which endowed the ALN-conjoined tetra-PEG hydrogel with depot formulation capacity for governing the on-demand release of ALN drugs. Consequently, the findings imply that these ALN-based tetra-PEG hydrogels mediate optimal release of therapeutic cargoes and effective promotion of in situ bone regeneration, which will be broadly utilized as therapeutic scaffolds in tissue engineering and regenerative medicine.